Ferroptosis and hearing loss: from molecular mechanisms to therapeutic interventions - Xingyi Lv; Chenyi Yang; Xianying Li; Yun Liu; Yu Yang; Tongyan Jin; Zhijian Chen; Jinjing Jia; Min Wang; Li Li (Journal of Enzyme Inhibition and Medicinal Chemistry)
Hearing loss profoundly affects social engagement, mental health, cognition, and brain development, with sensorineural hearing loss (SNHL) being a major concern. Linked to ototoxic medications, ageing, and noise exposure, SNHL presents significant treatment challenges, highlighting the need for effective prevention and regeneration strategies. Ferroptosis, a distinct form of cell death featuring iron-dependent lipid peroxidation, has garnered interest due to its potential role in cancer, ageing, and neuronal degeneration, especially hearing loss. The emerging role of ferroptosis as a crucial mediator in SNHL suggests that it may offer a novel therapeutic target for otoprotection. This review aims to summarise the intricate connection between ferroptosis and SNHL, offering a fresh perspective for exploring targeted therapeutic strategies that could potentially mitigate cochlear cells damage and enhance the quality of life for individuals with hearing impairments.